Toxico-Epidemiological Profile of Fatal Poisonings at a Tertiary Care Hospital in Visakhapatnam, India (2023): A Brief Report - Vinukonda Enos Nikhil; Manchala Jeevan Anudeep Babu; Mamatha Karanam; Dhannya Sasi; Kattamreddy Ananth Rupesh (National Board of Examinations Journal of Medical Sciences)
Suicide is a global issue in modern society, with people from different cultures exhibiting distinct behavioural patterns and methods. In recent times, suicide by pesticide poisoning has become a common occurrence in India. Generating data on the toxico-epidemiology of poisoning in each region is critical for implementing targeted interventions to restrict access to these substances and, in turn, prevent self-harm. The present study was conducted on fatal poisoning cases autopsied at a tertiary care hospital in Visakhapatnam during the year 2023. The study included 195 fatal poisoning cases, with 74.4% of the victims being male, and the majority falling within the 31–40 years age group. Pesticide consumption was responsible for 80% of all deaths, and 94.87% of the cases were intentional poisoning. The herbicide paraquat alone accounted for 39.4% of the deaths in the study population. Financial issues, familial disputes, and drug addiction were the primary reasons for suicides, and the survival period varied, with most individuals dying within 24 hours. Several Highly Hazardous Pesticides (HHPs) were used for these intentional self-harm cases, emphasizing the urgent need to restrict access to these substances to save lives as envisaged by the WHO.